2020
DOI: 10.1108/jec-09-2020-0168
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by necessity entrepreneurship, the case of Syrian refugees in Jordan

Abstract: Purpose This study aims to understand the challenges facing Syrian refugee entrepreneurs in Jordan and offers professional support to refugee entrepreneurs, with a view to improve their economic and social status, aid cultural integration and ultimately to help turn their business idea into reality. Design/methodology/approach A total of 62 semi-structured interviews were conducted with Syrian refugees in Jordan. Findings The study reveals that refugee entrepreneurs are both entrepreneurs of necessity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…However, some studies have suggested that the inclination to rely on the sense of belonging within co-ethnic enclaved groups might decrease the success of integration (Alrawadieh et al, 2019;Lewis, 2010). A recent study by Zighan (2020) explored some challenges faced by Syrian refugee entrepreneurs such as a lack of funds and access to financing, cultural barriers, inadequate access to business development, inadequate advisory and diagnostic support services, market access challenges, legal, regulatory and administrative barriers, a lack of innovation and technology adoption and development and a lack of management skills and capacity.…”
Section: Refugee Entrepreneurship Motives Challenge and Integrationmentioning
confidence: 99%
“…However, some studies have suggested that the inclination to rely on the sense of belonging within co-ethnic enclaved groups might decrease the success of integration (Alrawadieh et al, 2019;Lewis, 2010). A recent study by Zighan (2020) explored some challenges faced by Syrian refugee entrepreneurs such as a lack of funds and access to financing, cultural barriers, inadequate access to business development, inadequate advisory and diagnostic support services, market access challenges, legal, regulatory and administrative barriers, a lack of innovation and technology adoption and development and a lack of management skills and capacity.…”
Section: Refugee Entrepreneurship Motives Challenge and Integrationmentioning
confidence: 99%
“…(1) What are the socio-demographic characteristics of WHBB entrepreneurs in Pakistan? (2) What is the relationship between socio-economic characteristics, entrepreneurial income and family financial position of WHBB entrepreneurs in Pakistan?…”
Section: Research Questionsmentioning
confidence: 99%
“…Women's home-based entrepreneurship has been considered one of the most important drivers of economic growth in developed and developing economies [1,2]. Because of its scope, including work-life interaction and educating children [3], women's entrepreneurship has become a crucial aspect of the socio-economic transformation process [4], particularly in developing countries like Pakistan [5].…”
Section: Introductionmentioning
confidence: 99%
“…First, it provides an enhanced understanding of the effectiveness of informal businesswomen during economic crises. Second, within the sociocultural norms ( Zighan, 2021 ) in society, women can also increase their family and economic well-being by doing business at home even in the challenging times of a pandemic. Thirdly, these businesswomen can become role models for other women in society as it showed resilience to the COVID-19 pandemic.…”
Section: Discussion and Contributionmentioning
confidence: 99%